Smart Locker For Post Office - Perumal, Janapiriya A/P Raman; Dr. Nurul Aswa Binti Omar, Dr. Nurul Aswa Binti Omar (Applied Information Technology And Computer Science, 2022)
Internet of Things (IoT) is a network of physical, with a clear identification elements, sunset with intelligence software, sensors, and internet connection everywhere. Internet of Things also allows thing or even object to be control via applications that is connected to the internet. IoT have transpire the scheme of remotely monitoring objects through the Internet. The Arduino is a small, lightweight and cheap single board computer that can fit on human’s palm. Security plays a big role in a post office. Admin and staff concern about security by preventing any intruders to enter into the post office to stole money. The closed-circuit security camera, GPS location GSM(SMS), OTP password functions have been used to monitor to secure the valuable thing from third party. The problem faced by the post office are not being able to keep the money safe. There is a few post office break in cases occurs but the admin and staff is not able to take immediate action to prevent from theft or intruders entering the post office. Furthermore, the admin and staff unable to get any information like receiving notification whenever the intruders entering the post office. Therefore, to prevent from this situation a Smart Locker For Post Office is proposed. Objective of this project is to design MyLocker based on Internet of Things and Android studio which alerts the admin and staff of the post office. Other than that, to develop a system with piezo buzzer which is giving beep sound and send notification through mobile application to the admin and staff because it helps to improve the security to prevent from unauthorized unlocking the locker. Moreover, to design the system by perform testing the functionality of the system on receiving and display the data given from the hardware to the admin and staff(user) of the post office through mobile. The scope of the project is mainly to alert the admin and staff about the unauthorized unlocking of the locker. The alert is programmed to be sending location to mobile called GPS and there is a message function to send notification called GSM. Furthermore, it is also to overcome frauds. The methodology that have been used to build this Smart Locker For Post Office is Waterfall Model. This system is encrypted with the GSM /GPS modem, vibration sensor, camera with OTP number. For example, the GPS modem of the locker will read the information of location for every five seconds and compare against the predefined location. If the location is match it will send one time password to unlock the locker. Furthermore, a mobile application also be developed for register, login and verification purpose. Apart from that to be more secured, OTP password is incremented in this system. Moreover, a spy camera had been incremented where it will alert the presence of the third party who are trying to access the locker without authentication at different location. The alert will send to admin side app. Lastly, there is also a message function in this locker system. The purpose of this message function is to alert or trigger the client if any theft or fraud who tried to break the locker. Notifications will also be sent to the user immediately when motions are detected. So, this system will be more secured and easy to implement. There are some suggestions for future work to improvise the system development on proposed project which are adding fingerprint reader to provide high security which is prominent to prevent from unauthorized third party. Furthermore, implement face recognition algorithms which is able to verify user faces to access the locker. Last but not least, enhancing interface using UI design where it improve the looks and feel of the mobile application for Smart Locker System with more attractive design for users.